2016
DOI: 10.1027/0227-5910/a000393
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on the Efficacy of Volunteer Mentorship for Young Adults With Self-Harm Behaviors Using a Quasi-Experimental Design

Abstract: Postdischarge care provided by volunteers showed significant improvement in hopelessness and depression. Volunteers have been commonly involved in suicide prevention services. Further research using rigorous methods is recommended for improving service quality in the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…The majority employed a pre-test/post-case series study design (k = 11; 57·9%) [73], [74], [75], [76], [77], [78], [79], [80], [81], [82], [83]. Sixteen (84·2%) recruited participants from community mental health services or hospitals, including inpatient and emergency department settings [73], [74], [75], [76], [77], [78], [79], [80], [83], [84], [85], [86], [87], [88], [89], [90], [91]. Interventions included DBT, CBT, and brief contact interventions.…”
Section: Resultsmentioning
confidence: 99%
“…The majority employed a pre-test/post-case series study design (k = 11; 57·9%) [73], [74], [75], [76], [77], [78], [79], [80], [81], [82], [83]. Sixteen (84·2%) recruited participants from community mental health services or hospitals, including inpatient and emergency department settings [73], [74], [75], [76], [77], [78], [79], [80], [83], [84], [85], [86], [87], [88], [89], [90], [91]. Interventions included DBT, CBT, and brief contact interventions.…”
Section: Resultsmentioning
confidence: 99%
“…A training manual has also been developed and tested by Dr. Y. W. Law. An evaluation study on the efficacy of the scheme found the intervention group to have realized significant improvements in hopelessness and depressive symptoms (Law et al, 2016), thus demonstrating the potential of the mentorship programs in providing effective follow-ups and community support to the vulnerable individuals, in particular to those discharged from the Accident and Emergency Departments of the public hospitals. Dr. Y. W. Law and the team are in collaboration with the medical professionals to conduct a randomized controlled trial on a three-pronged model that recognizes the central role of social connectedness in addressing discharged patients who have engaged in self-harm behaviors and incorporates technology-based, standardized self-help, personal human connections, and community-based interventions with clinical treatment.…”
Section: Indicated Levelmentioning
confidence: 96%
“…Ongoing follow-ups and community support are effective in reducing suicide deaths and attempts among the patients who have recently been discharged (Luxton, June, & Comtois, 2013). In the hope of providing a support service to the youths who have engaged in deliberate self-harm behaviors and have been discharged, the CSRP has initiated a volunteer mentorship scheme (Law et al, 2016) based on the social work empowerment approach. This involves a team of volunteer mentors being provided with on-the-job training in such skills as the provision of clinical consultation and professional advice by the experienced social workers, psychiatrists, and psychologists.…”
Section: Indicated Levelmentioning
confidence: 99%
“…8,9,[58][59][60][61][62][63] Ten programs were specifically aimed at decreasing the amount of time healthcare providers spent completing non-clinical tasks, such as provision of comfort items and assistance with meals, hydration, mobility and transportation once they were ready for ED discharge. 15,[49][50][51][52][53][54][55][56][57] The majority (n=52; 59.8%) of described programs had general volunteers in the ED, while 35 (40.2%) had volunteers targeting a specific patient population, including pediatrics, 17,42,[64][65][66][67][68][69][70][71][72][73][74][75][76] geriatrics, 25,[38][39][49][50][51][52]77 patients with mental health and addiction issues 18,[22][23][24]35,40,…”
Section: Volunteer Characteristics and Activitiesmentioning
confidence: 99%
“…12 programs used quantitative methods, including a number of randomized clinical trials, 18,19,24,26,37,40,42,50,52,53,77,79 four programs used qualitative methods 12,13,20,25 and two programs did not specify the type of evaluation used 23,31 . Of those that reported a focus on particular outcomes, patient satisfaction, 12,13,20,31 follow-up and referral rates, 25,40,79 ED and hospital costs and length of stay, 19,42,77 subsequent ED visits, 26,37 medical complications, 50,52 mental health , 18,23,24 and malnutrition 53 in the hospital were all reported to be positively affected by volunteers in the ED. Many of the evaluations of programs took the form of surveys and questionnaires from the perspectives of patients and hospital staff.…”
Section: Outcomes Measured Within Evaluated Programsmentioning
confidence: 99%